Hubungan Kebiasaan Berkemih Dengan Kejadian Overactive Bladder (OAB) Pada PerawatWanita Di Rumah Sakit Bhayangkara Mataram - Nia Firdianty Dwiatmojo; Kadek Mega Mutiara Sari Putri; Agus Putradana; Eva Marvia; Alwan Wijaya (LPPM STIKES Mataram, 2024)
Introduction: Overactive Bladder (OAB) is a chronic clinical syndrome associated with symptomatic urgency without urinary incontinence, urinary tract infection, or other pathological conditions. Psychological factors such as stress, depression, and anxiety can trigger OAB. OAB is more common in women than men. Nurses, especially women, are more likely to experience OAB due to poor working conditions and urinary habits. The Stress and psychological burden felt by female nurses at work is significantly related to the incidence of OAB. Objective: he research design used in this study was correlation analysis with a cross-sectional design. The population in this study were all female nurses at Bhayangkara Hospital in MataraMethod: This study is a descriptive correlational study, with a cross-sectional approach. The sampling technique is total sampling with a sample size of 50 nurses. Result: The results showed that out of 50 respondents, 32 respondents did not have OAB. This can be seen from the urinary habits of the 32 respondents who were quite good. Statistical test results from Spearman correlation obtained a significant number or Sig (2-Tailed) value of 0.644 which means <0.05. Conclusion: there was no significant correlation between urinary habits with the incidence of OAB among female nurses at Bhayangkara Hospital, Mataram.